Palaeoamyda messeliana nov. comb. (Testudines, Pan-Trionychidae) from the Eocene Messel Pit and Geiseltal localities, Germany, taxonomic and phylogenetic insights - Edwin Cadena (PeerJ, 2016)
Background Abundant pan-trionychid (soft-shell) turtles specimens have been found in Eocene sequences of central Europe, particularly from two localities in Germany, the Messel Pit (a UNESCO World Natural Heritage Site) and Geiseltal, traditionally attributed to Trionyx messelianus or Rafetoides austriacus. Over the last two decades new specimens of this taxon from these two localities have been discovered and fully prepared. However, they have remained unstudied, as well as their phylogenetic position inside Pan-Trionychidae is unknown. Results Five new specimens of Palaeoamyda messeliana nov. comb. from Messel Pit and Geiseltal localities are fully described here. A revised diagnosis for the species is also presented here, together with its inclusion in a phylogenetic analysis of Pan-Trionychidae that shows that this species is sister to the extant Amyda cartilaginea, one of the most abundant pan-trionychid (soft-shell) turtles from Asia, both members of the clade Chitrini. The specimens described in here are among the best and most complete fossil pan-trionychid skeletons so far known.